2015
DOI: 10.1155/2015/537598
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biosourced Alkyd Nanoemulsions as Drug Carriers

Abstract: Novel oil-in-water (O/W) nanoemulsions were formulated using short, medium, and long oil length alkyds synthesized from palm kernel oil by a two-stage alcoholysis-polyesterification reaction. Alkyd/surfactant/water ternary phase diagrams identified a composition of 1% alkyd, 9% Tween 80, and 90% water where spontaneous production of nanoemulsions occurred. The pH, droplet size, and zeta potential of all formulations were in the range of 6.4–6.6, 11–14 nm, and −6 mV to −8 mV, respectively. Rheological studies s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…There was also a slight increase in the zeta potential (−9.78 ± 0.97 to −11.94 ± 1.52 mV) on storage at 40 ± 2 °C and 75 ± 5% RH for 3 months. Previous studies have reported a decrease in the magnitude of zeta potential [39]. The data are presented as the mean ± SD, n = 3.…”
Section: Stability Studiesmentioning
confidence: 99%
“…There was also a slight increase in the zeta potential (−9.78 ± 0.97 to −11.94 ± 1.52 mV) on storage at 40 ± 2 °C and 75 ± 5% RH for 3 months. Previous studies have reported a decrease in the magnitude of zeta potential [39]. The data are presented as the mean ± SD, n = 3.…”
Section: Stability Studiesmentioning
confidence: 99%
“…The viscosity of IMQ-loaded NE (NE1-NE4) remained constant with an increase in the rate of shear (>15 s −1 ) and exhibited Newtonian fluid behavior [28]. This is indicative of the unrestricted flow of droplets in the direction of the shearing force [29].…”
Section: Characterization Of Imq-nementioning
confidence: 99%
“…Bhd., Selangor Darul Ehsan, Malaysia) resulting in spontaneous formation of nanoemulsions. 15 Phenytoin-loaded alkyd nanoemulsions were prepared by dissolution of the drug in the oil phase (alkyd) before combining with Tween 80 and water, to produce final phenytoin concentrations in the nanoemulsion of 3.125, 6.25, 12.5, 25, 50, 100, and 200 mg/mL.…”
Section: Preparation Of Phenytoin-loaded Alkyd Nanoemulsionsmentioning
confidence: 99%
“…We recently reported the advantages of short oil length alkyd nanoemulsions as vehicles for topical application of hydrophobic drugs due to their ease of preparation by phase inversion, consistent nanodroplet size around 13 nm, physical stability on long-term storage, and favorable biocompatibility as demonstrated in fibroblast cell culture. 15 In the present study, alkyd nanoemulsions incorporating phenytoin were characterized in terms of their physicochemical properties and their effect on the proliferation of human epidermal skin cells in vitro to evaluate their potential utility for topical wound-healing applications.…”
Section: Introductionmentioning
confidence: 99%